Mapping of Subsurface Geological Structure and Land Cover Using Microgravity Techniques for Geography and Geophysic Surveys: A Case Study of Maluri Park, Malaysia - La Ode Nursalam; A Arisona; R Ramli; La Harudu; Sitti Kasmiati; Eko Harianto; Fahrudi Ahwan Ikhsan; Andri Estining Sejati (Geosfera Indonesia, 2019)
A microgravity investigation on bedrock topography was conducted at Maluri park reference level in Kuala Lumpur, Malaysia. The study aim to mapping the near-surface structure and soil and land cover distribution for geography and geophysics surveys. Two types of cross-section modeling of the residual anomaly generated the MaluriBouguer Anomaly model for site-1 and site-2 at Maluri Park. The 2D microgravity models produced the contour map, displaying the characterization due to density contrast in rock types while mapping the subsurface geological structure at different depths. Moreover, a synthetic model was initiated with the assumption of lateral distance on the left and right sides taken at 50 m and a depth of 60 m. The results of modeling confirmed that the soil and rock type composition on both models site tests are topsoil (1.1 to 1.92 g/cm3), soil (1.8 g/cm3), clay (1.63 g/cm3), gravel (1.7 g/cm3), sand (2.0 g/cm3), shale (2.4 g/cm3), sandstone (2.76 g/cm3), and limestone (2.9 g/cm3). The 2D gravity modeling using two model site tests obtained a correspondence with the observed microgravity data. Keywords: Bouguer anomaly, limestone, microgravity, soil structure, topography. References Amaluddin, L. O., Rahmat, R., Surdin, S., Ramadhan, M. I., Hidayat, D. N., Purwana, I. G., & Fayanto, S. (2019). The Effectiveness of Outdoor Learning in Improving Spatial Intelligence. Journal for the Education of Gifted Young Scientists, 7(3), 667–680. https://doi.org/10.17478/jegys.613987 Arisona,A., Mohd N., Amin E.K., &Abdullahi, A.(2018).Assessment of microgravity anomalies of soil structure for geotechnical 2d models.Journal of Geoscience, Engineering, Environment, and Technology (JGEET)3(3), 151-154. Georgsson, L.S. (2009). Geophysical Methotds Used in Geothermal Exploration. Presented at Exploration for Geothermal Resources, 1-22 November 2009, 1-16. Grandjean, G. (2009). From Geophysical Parameters to Soil Characteristics.Florida: Report N°BRGM/FP7-DIGISOIL Project Deliverable 2.1, Final ReportDepartment of Civil and Coastal EngineeringUniversity of Florida. Hiltunen, D.R., Hudyma,N.,Tran,K.T.,&Sarno,A.I. (2012).Geophysical Testing of Rock and Its Relationthipsto Physical Properties.Florida:Final ReportDepartment ofCivil and Coastal EngineeringUniversity ofFlorida. Kirsch,R. (2006).GroundwaterGeophysics, ATool for Hydrogeology.New York: Springer. Kamal,H.,Taha,M.,&Al-Sanad,S. (2010). Geoenvironmental Engineering and Geotechnics, GeoShanghai 2010 International Conference. (accessed 02.03.17) Lilie, R.J. (1999).Whole Earth Geophysics: An Introductory Textbook for Geologists and Geophysicists. New Jersey:Prentice-HallInc. Pringle, J.K., Styles, P., Howell, C.P.,Branston, M.W., Furner, R., &Toon,S.M. (2012). Long-term time-lapse microgravity and geotechnical monitoring of relict salt mines, marston, cheshire, uk. Geophysic77(6), 165-171. Samsudin, H.T.(2003).A microgravity survey over deep limestone bedrock.Bulletin of Geological Society of Malaysia4(6), 201-208. Tan, S.M. (2005). Karsticfeatures of kualalumpur limestone. Bulletin of the Institution of EnginnerMalaysia 4(7), 6-11. Tajuddin, A.&Lat, C.N. (2004).Detecting subsurfacevoids using the microgravity method, a case study from kualalipis, pahang.Bulletin of Geological Society of Malaysia 3(48), 31-35. Tuckwell, G., Grossey, T., Owen, S., & Stearns, P. (2008). The use of microgravity to detect small distributed voids and low-density ground. Quarterly Journal of Engineering Geology and Hydrogeology, 41(3), 371–380. https://doi.org/10.1144/1470-9236/07-224 Wanjohi, A.W. (2014). Geophysical Field Mapping. Presented at Exploration for Geothermal Resources, 2-23 November 2014, 1-9. Yusoff , Z.M., Raju,G. &Nahazanan, H.(2016).Static and dynamic behaviour of kualalumpur limestone. Malaysian Journal of Civil Engineering Special Issue Vol.28 (1), p.:18-25. Zabidi, H. & De Freitas, M.H. (2011).Re-evaluation of rock core logging for the prediction of preferred orientations of karst in the kualalumpur limestone formation. Engineering Geology, 117(3-4), p.: 159–169. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License